SIMULATION OF OPEN MECHANISMS FOR THE ADDITIVE PROCESS WELD PLASTICS - N. N. Hurski; V. A. Skachek; A. V. Skachek; Y. A. Skudnyakov (Системный анализ и прикладная информатика)
This article discusses: model of the two-link mechanism; generalized scheme of mechatronic simulation model of 3D-printer with the positioning units of electric DC; mathematical model of the actuator of the printer unit in the form of a system of differential equations; 3D-printer programming model implemented in the Matlab-Simulink environment using the c standard library blocks and SimMechanics library; virtual (animated) 3D printer model on the basis of the library Simulink 3D Animation, supports the visualization of the movements of the designed mechanism of the basic units. We present the initial data and the results of simulation of 3D-printer type Scara as a waveform positioning actuator (extruder) in the manufacture of test items by fusing plastic.